Comparison of the survival outcomes of laparoscopic, abdominal and gasless laparoscopic radical hysterectomy for early-stage cervical cancer: trial protocol of a multicenter randomized controlled trial (LAGCC trial) - Tang, Xiaoyan; Zhou, Shan; Zhang, Xuyin; Hua, Keqin; He, Yuan; Wang, Ping; Teng, Yincheng; Feng, Weiwei (Frontiers in Oncology, 2023)
Background: Radical hysterectomy (RH) is considered a cornerstone in the treatment of early-stage cervical cancer. However, the debate surrounding the optimal surgical approach, whether minimally invasive or open surgery, remains controversial. The objective of this trial is to evaluate the survival outcomes of cervical cancer patients who undergo different surgical approaches.Methods: This study is designed as a prospective, multicenter, open, parallel, and randomized controlled trial. A total of 500 patients diagnosed with stage IA1 with LVSI, IA2, IB1, or IB2 (2018 FIGO) will be recruited. Recruitment of participants started in November 2020. The participants will be randomly assigned to one of three groups: conventional laparoscopic RH, gasless laparoscopic RH, or abdominal RH. The primary endpoint of this trial is the 2-year disease-free survival (DFS) rate. The secondary endpoints will include the 2-year overall survival (OS) rate, 5-year DFS/OS, recurrence rates, operation time, intraoperative blood loss, surgery-related complications, and impact on quality of life (QoL).Discussion: We expect this trial to provide compelling and high-quality evidence to guide the selection of the most appropriate surgical approach for early-stage cervical cancer.